Empowerment Of Batik Small And Medium Industries By The Trade And Industry Office In Jatipelem Village Jombang Regency - Wulan Nur Fath-Hiah; Ananta Prathama (UNIVERSITAS PAKUAN, 2024)
Indonesia is one of the developing countries that has a national commitment to improve development in the economic sector. Small and medium industries are an alternative designed by the government as one of the programs that aims to help national economic growth with the help of the business sector in order to strengthen the local economy so that it can absorb labor. One of the small and medium industries that has always been the talk of the town is Batik. This is because besides being a work of art, batik is also a promising industry to be developed. Jombang Regency has a distinctive batik that has become an icon of Jombang Regency itself. The purpose of the research is to find out how the process of empowering small and medium batik industries by the Trade and Industry Office in Jatipelem Village, Jombang Regency. The research method used is descriptive qualitative with an observation and interview approach. The results showed that there were empowerment efforts made by the Jombang Regency Trade and Industry Office in supporting the batik business in Jatipelem Village. This empowerment is in the form of coaching, providing access to capital, marketing, and providing protection for the batik business. From the results of the study, it can be concluded that there is empowerment of batik small and medium industries carried out by the Jombang Regency Trade and Industry Office, but there are still several obstacles so that this empowerment has not run optimally.